2018
DOI: 10.1177/1533317517739384
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitter Pathway Genes in Cognitive Decline During Aging: Evidence forGNG4andKCNQ2Genes

Abstract: Background/Rationale: Experimental studies support the role of neurotransmitter genes in dementia risk, but human studies utilizing single variants in candidate genes have had limited success. Methods: We used the gene-based testing program Versatile Gene-based Association Study to assess whether aggregate variation across 6 neurotransmitter pathways influences risk of cognitive decline in 8159 cognitively normal elderly (≥65 years old) adults from 3 community-based cohorts. Results: Common genetic variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 74 publications
0
21
0
Order By: Relevance
“…The role of the Kv7.2 channel in neurodegeneration is not the focus of this review; however, it is interesting to note that common genetic variation in KCNQ2 has recently been associated with risk of cognitive decline in healthy elderly (Bonham et al, 2018). Furthermore, some evidence exists for an (indirect) role of Kv7.2 in neurodegeneration disorders.…”
Section: The Role Of Kv72 Channels In Neurodegenerationmentioning
confidence: 99%
“…The role of the Kv7.2 channel in neurodegeneration is not the focus of this review; however, it is interesting to note that common genetic variation in KCNQ2 has recently been associated with risk of cognitive decline in healthy elderly (Bonham et al, 2018). Furthermore, some evidence exists for an (indirect) role of Kv7.2 in neurodegeneration disorders.…”
Section: The Role Of Kv72 Channels In Neurodegenerationmentioning
confidence: 99%
“…Guanine nucleotide binding-protein γ subunit 4 (GNG4) is a member of the G-protein trimer complex, and was first identified as the brain-specific subunit ( 13 ). In the human brain, GNG4 is more highly expressed in the hippocampus compared with in other brain regions, and GNG4 expression is reduced with advanced age, which suggests that GNG4 is associated with cognitive decline ( 14 ). A previous study has suggested that GNG4 is hypermethylated and notably decreased in glioblastoma (GBM) ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…GRIN1 and GRIN2D encode different subunits of the Mmethyl-D-aspartate (NMDA) receptor, which is a heteromeric glutamate-gated calcium ion channel essential for synaptic function in the brain [29,30]. Similarly, GNG4 has been linked functionally to synaptic plasticity and cognitive function [31,32], whereas adenylyl cyclases have been described to modulate markers of synaptic activity [33]. In the same way, neuroligins function as trans-synaptic adhesion molecules with a known role in synaptogenesis [34] and DLGAP1-4 interacts with members of the PSD95 family, NMDA receptors, and Shakertype potassium channels to contribute to homeostatic synaptic plasticity [35].…”
Section: Discussionmentioning
confidence: 99%
“…Gene-set enrichment analysis based on Reactome dataset [27] also identified four significantly enriched groups (FDR < 0.01), including neuronal system, metabolism, signal transduction, and proteinprotein interactions at synapses (Additional file 3: Table S4). According to this classification, eight genes with a significant hypomethylation profile were identified to be involved in neuronal signal transduction, mostly at synaptic level (i.e., GRIN1, GRIN2D, GNG4, ADCY8, NLGN2, DLGAP1, DLGAP2, and PTPRD) [29][30][31][32][33][34][35][36] (Fig. 4).…”
Section: Episignature Of Rmns Is Enriched With Genes Involved In Neurmentioning
confidence: 99%